2004
DOI: 10.2135/cropsci2004.5000
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Winter Hardiness in 10 Lentil Recombinant Inbred Line Populations

Abstract: Available winter hardy lentil (Lens culinaris Medik.) germplasm has prompted interest in the development and use of cultivars that can be fall planted in cold highland areas. This change in production of lentil from normally spring sown to fall sown is environmentally sound and increases yield potential. Understanding the mode of inheritance of winter hardiness in lentil would assist breeding efforts. The objectives of this study were to determine the inheritance and heritability of winter hardiness in lentil.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 21 publications
1
4
0
1
Order By: Relevance
“…The present linkage map defined positions of 216 polymorphic genomic SSR markers which were distributed on 7 linkage groups spanning 1183.7 cM distance with an average marker density of 5.48 cM. The map length was comparable to other intraspecific linkage maps of lentil (784.1 cM; [ 50 ], 1192 cM; [ 51 ], 1868 cM; [ 52 ], 1565.2 cM; [ 27 ]) with the added advantage of being denser than these maps. Among the 7 linkage groups, each group differed from the other with respect to length and marker distribution as a result of which some groups were densely populated (LG1 and LG3), while some exhibited few markers (LG7 and LG6) which could be explained by the fact that SSRs are ubiquitously and randomly distributed in plant genomes.…”
Section: Discussionsupporting
confidence: 55%
“…The present linkage map defined positions of 216 polymorphic genomic SSR markers which were distributed on 7 linkage groups spanning 1183.7 cM distance with an average marker density of 5.48 cM. The map length was comparable to other intraspecific linkage maps of lentil (784.1 cM; [ 50 ], 1192 cM; [ 51 ], 1868 cM; [ 52 ], 1565.2 cM; [ 27 ]) with the added advantage of being denser than these maps. Among the 7 linkage groups, each group differed from the other with respect to length and marker distribution as a result of which some groups were densely populated (LG1 and LG3), while some exhibited few markers (LG7 and LG6) which could be explained by the fact that SSRs are ubiquitously and randomly distributed in plant genomes.…”
Section: Discussionsupporting
confidence: 55%
“…Kahraman et al (2004a) developed ten recombinant inbred line (RIL) populations from cold tolerant by sensitive parents. The population was evaluated for winter survival at one location in Washington State, and two locations in Turkey.…”
Section: Abiotic Stress Tolerancementioning
confidence: 99%
“…Genetic studies on winter hardiness of lentil, using recombinant inbred line populations, indicated that the trait is controlled by several genes (Kahraman et al, 2003). Winter hardiness in pea ( Pisum sativum L.) is reportedly controlled by dominant genes (Cousin et al, 1985) and additive genes (Auld et al, 1983).…”
mentioning
confidence: 99%